Teaching measurement: The role of mathematics teachers' enacted PCK on gain in learner outcomes - Hanlie Botha; Corene Coetzee; Liezell Zweers (Jurnal Infinity, 2023)
Teaching is a challenging profession where teachers must create valuable learning opportunities to enhance learners’ conceptual understanding. Apart from mathematical content knowledge, teachers use their pedagogical content knowledge (PCK) that develops as they reflect on previously taught lessons and learner responses in assessments. International and national assessment studies showed that South African learners perform poorly in, among other topics, Measurement. Thus, we determined the gain in learner outcomes as revealed in a pre-and post-test on Measurement and studied one of the PCK domains, namely teachers’ enacted PCK as informed by the baseline assessment learner outcomes. The aim was to determine how teachers’ enacted PCK relate to learner outcomes. Underpinned by a social constructivist paradigm, the study used a mixed-method research approach. Data were gathered from a pre-and post-test written by 124 Grade 9 learners taught by two experienced mathematics teachers in a city school in South Africa. Findings revealed that although some improvements are evident after the topic has been taught, the test was still experienced as difficult by almost all the learners. However, from the observations, there is little evidence that the experienced teachers extensively used the baseline assessment outcomes to inform their teaching.